WATER ASSOCIATED DISEASES AMONGST CHILDREN in IDPs CAMPS AND THEIR RELATION TO FAMILY ECONOMICS STATUS: CASE STUDY OF ABUSCHOCK IDPs CAMP, NORTH DARFUR STATE, SUDAN - Soliman, Adam Ahmed; Abdulrahman, Badreldin Mohamed Ahmed; Abdalla Ali, Jamal; Abdelaziz, Afrah Ibrahim (International Journal of Research -GRANTHAALAYAH, 2017)
This research discussed water-associated diseases amongst children in IDPs camps and their relation to family economic status in Abushock IDPs Camp, North Darfur State, Sudan. The main purpose of the research was to explore wither there exist a relationship between the family economic status and the rate of infection of its children with water transmitted diseases. Primary data were obtained from a total 140 of respondents who were selected using multi-stage sampling technique. Secondary data were obtained from published materials like journals, books and other relevant materials. Statistical packages for social sciences (SPSS) were used to display and interpret the data. The results revealed that water pollution in the study area is not related to the water sources, but due to the ways used to transport water, stored, and handling. Furthermore, there a declining in the rate of deaths among children related to water borne diseases due to wide spread medical services centers wither publically or privately owned, or owned by non-governmental organizations (NGOs). Chi-Square test showed that there exist a statistical significant relationship at 0.05 level between the economic status of the internally displaced family and the level of water-associated diseases prevalence among its children. It also shows that there exist a statistical significant relationship at 0.05 level between the economic status of the internally displaced family and its accessibility to potable water.